Proposal of an alternative diet as an element of improving the safety and quality of nutrition for soldiers - Kler Paweł; Sobczuk Sebastian; Hlubik Jan; Bertrandt Jerzy (2022)
In a specific community, which is also formed by soldiers, the diet used should satisfy all nutritional needs, using physically and economically available foodstuffs (products, dishes). It can be called a basic diet. However, in certain situations, which include the spread of modern-age diseases, as well as possible difficulties in obtaining previously available food products due to the crisis caused by the ongoing war behind the Poland's eastern border, the use in a prudent manner of alternative diets should be considered. The article presents a proposal for an exemplary pescatarian diet, which can be classified as an alternative diet. The purpose of this publication is to develop menus for a diet that can provide an alternative food standard for soldiers in the context of improving the assurance of the quality of their nutrition. The research problem included in the paper is the following question: how can alternative diets improve the soldiers' nutrition quality assurance? The publication uses the necessary research theoretical methods: analysis, synthesis and inference, and empirical methods: document examination and computer modeling to develop menus for an alternative diet. The considerations carried out in the publication and the proposal of a menu for an alternative diet – pescatarian – prove its positive influence on preventing the spread of diet-related modern-age diseases, which translates into the health of military personnel, and consequently allows to maintain the required physical fitness of soldiers and their availability during military service and performance of assigned tasks.